2005
DOI: 10.1542/peds.2004-0815g
|View full text |Cite
|
Sign up to set email alerts
|

Age-Related Changes in Sleep/Wake Patterns Among Korean Teenagers

Abstract: This study clearly demonstrates that Korean adolescents do not get adequate sleep and that they have profound discrepancies in their sleep/wake patterns between school and weekend nights. Compared with previous studies from other countries, Korean students display even greater sleep deprivation and also more irregular sleep/wake patterns. This study also demonstrates that academic demands/stress and early school start time are the most important contributing factors for sleep deprivation among Korean adolescen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

33
249
6
6

Year Published

2006
2006
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 339 publications
(294 citation statements)
references
References 18 publications
33
249
6
6
Order By: Relevance
“…In a nationally representative sample of 136,589 high school students in South Korea (ages 13-18 years), 43 % reported a daily sleep duration of fewer than 6 h and only 7 % reported obtaining 8 or more hours of sleep (Do et al 2013). Another study of South Korean adolescents found that total sleep time decreased by approximately 3 h from fifth to twelfth grade, with the average school-night sleep duration being only 4.86 h among twelfth grade students (Yang et al 2005). These studies are in line with a meta-analysis examining geographic differences in sleep duration among adolescents from 23 countries, which found adolescents from Asian countries to sleep 40-60 min less on school nights than adolescents from the US, who in turn sleep 20-60 min less on school nights than adolescents from Europe or Australia (Olds et al 2010).…”
Section: Cultural Factorsmentioning
confidence: 99%
“…In a nationally representative sample of 136,589 high school students in South Korea (ages 13-18 years), 43 % reported a daily sleep duration of fewer than 6 h and only 7 % reported obtaining 8 or more hours of sleep (Do et al 2013). Another study of South Korean adolescents found that total sleep time decreased by approximately 3 h from fifth to twelfth grade, with the average school-night sleep duration being only 4.86 h among twelfth grade students (Yang et al 2005). These studies are in line with a meta-analysis examining geographic differences in sleep duration among adolescents from 23 countries, which found adolescents from Asian countries to sleep 40-60 min less on school nights than adolescents from the US, who in turn sleep 20-60 min less on school nights than adolescents from Europe or Australia (Olds et al 2010).…”
Section: Cultural Factorsmentioning
confidence: 99%
“…Com exceção dos estudos de Saarenpää-Heikkilä et al (18) e de Thorleifsdottir et al (15) , todos os trabalhos apresentaram desenho transversal. Na Tabela 1 encontra-se a síntese dos principais estudos analisados (3,5,7,(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28) . As escalas de sonolência Epworth Sleepiness Scale e a School Sleep Habits Survey foram as mais utilizadas para análise da sonolência diurna excessiva.…”
Section: Estudos Sobre Sonolência Diurna Excessivaunclassified
“…Houve somente associação entre sonolência diurna excessiva e insônia para o sexo masculino. Já no estudo de Petry et al (23) , a prevalência encontrada foi de 7,8%, sendo os problemas respiratórios e o baixo desempenho escolar os principais fatores associados. De forma geral, os estudos com amostras brasileiras não são conclusivos quanto às prevalências e aos principais fatores associados à sonolência diurna excessiva.…”
Section: 1 Sexounclassified
“…studies have clearly shown [1][2][3][4][5][6][7] that children are highly unlikely to obtain sufficient sleep on a stable and regular schedule. two polls by the National sleep Foundation 1,2 indicated that parents routinely overestimate their children's sleep duration, and that, in fact, children sleep much less than what was deemed appropriate for their stage of development.…”
Section: The Conglomerate Of Multifactorial Components Potentially Comentioning
confidence: 99%